Gambaran Tingkat Kecemasan Mahasiswa Akhir Perpanjangan Studi Dalam Menghadapi Skripsi Di Program Studi Ilmu Keperawatan Unsrat - Mogea, Grasela; Kristamuliana; Renteng, Septriani (Mapalus Nursing Science Journal, 2024)
Background Anxiety during the process of working on the thesis certainly makes the condition uncomfortable. This discomfort results in disruption of the ability to concentrate and the ability to deal with problems during the work process. The purpose of this research is to know the description of the level of anxiety of students at the end of extended studies in dealing with thesis in the Unsrat Nursing Study Program. Thismethod Research design This type of research uses descriptive research with survey methods. A sample of 30 respondents was obtained using the Total Sampling technique.  The results of the study obtained data that almost all respondents had a mild level of anxiety, namely as many as 15 people (50.0%). Conclusion Based on the results of data analysis, the level of student anxiety at the end of the extension in the preparation of thesis to write a thesis, namely difficulties such as statistical tests, as well as feelings of pessimism, laziness, and lack of enthusiasm. Suggestion Increase awareness that research substance is part of the things that must be mastered by making notes, summarizing, and studying before determining research problems, can make a schedule during the process of writing a thesis. Keywords: Student, Anxiety